Manajemen Impressi Dalam Membangun Reputasi Kantor Pertahanan Kabupaten Bengkulu Utara - refika masta nora (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2019)
This research is motivated by the general negative view of the community about services throughout the Land Office which considers that land certification services are complicated, expensive, and require a long time. In addition, public perceptions of the prona program allegedly involved illegal payments by some program implementers so as to reduce the reputation value for the National Land Agency of the Republic of Indonesia. The issues raised in this study are First, How is reputation established in service at the North Bengkulu Regency Land Office. Second, how is the strategy in managing public service reputation in the North Bengkulu Regency Land Office. This study uses a qualitative approach with a constructivism paradigm and with in-depth interview data collection techniques, participant observation and documentation studies. The results showed that there were several factors that influenced the building of reputation for the North Bengkulu Land Office, namely: improving product quality, client relations, corporate culture, fulfilling contracts, leadership style, building media profiles and disclosing information to the public in accordance with the disclosure laws. information. In managing reputation, organizational self-presentation with impression management theory is important for the National Land Agency of North Bengkulu Regency in forming a positive image in various circles.